ANALISIS OF THE USE OF THE SAMESING ELEMENTS FAST-TRACK-TO SURGERY TREATMENT TO PATIENT WHICH WIDESPREAD PERITONITIS - V. Yu. MYKAHYLICHENKO; Yu. I. BASNAEV; N. E. KARAKURSAKOV (Кубанский научный медицинский вестник, 2017)
The analysis of the effectiveness of the use of certain elements of fast-track-surgery in the treatment of patients with acute surgical pathology, complicated widespread peritonitis. To this end, during the analysis, patients were divided into two groups: the first (control) assigned 35 patients (retrospective analysis of case histories), whose treatment was carried out in the normal way – surgery, adequate antibiotic therapy, conventional infusion therapy, analgesics. The second group (basic) – 35 patients whose treatment was supplemented by some elements of the fast-track-surgery. Clinical and laboratory evidence of accelerated recovery of normal intestinal motility, protein index lesser than the complications in the first group relative to the second. conclusion about the effectiveness of the elements can be made on the basis of the data fast-track-surgery in the treatment of patients with acute surgical pathology, complicated widespread peritonitis.